2022
DOI: 10.1002/aelm.202100984
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility and Photo‐Bias Stable Metal Oxide Thin‐Film Transistors Engineered by Gradient Doping

Abstract: Doping of oxygen‐deficient binder is an efficient way to alleviate the photo‐bias instability issue of oxide thin‐film transistors (TFTs). However, almost all dopants are working as electron suppressors and degrading mobility. Here we report an effective three‐level O‐anti|O|O‐N (OI|OII|N) gradient doping solution to overcome the adverse mobility‐stability trade‐off in N‐doped InGaZnO (IGZO:N) TFTs. 100 nm‐thick IGZO:OI|IGZO:OII|IGZO:N (IGZO:OI|OII|N) junctionless channel layers are fabricated by varying the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Exploring nonstoichiometric compositions of a-IGZO (with greater or lesser relative concentrations of the In, Ga, and/or Zn metal constituents compared to 111 a-IGZO) is an active area of research for improving upon a-IGZO TFT characteristics such as field effect mobility. [40][41][42][43][44][45] These efforts are sometimes linked to the deposition of bilayer [46][47][48][49][50] (or trilayer) [51][52][53] active channels. These bilayer TFTs often contain a stoichiometric or near-stoichiometric stability layer [43] with a boost layer that is richer in certain constituent elements such as In, [45,49] doped with metals such as Ti, [54] or composed of a conductive material such as ITO [55] ) intended to enhance the TFT electrical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring nonstoichiometric compositions of a-IGZO (with greater or lesser relative concentrations of the In, Ga, and/or Zn metal constituents compared to 111 a-IGZO) is an active area of research for improving upon a-IGZO TFT characteristics such as field effect mobility. [40][41][42][43][44][45] These efforts are sometimes linked to the deposition of bilayer [46][47][48][49][50] (or trilayer) [51][52][53] active channels. These bilayer TFTs often contain a stoichiometric or near-stoichiometric stability layer [43] with a boost layer that is richer in certain constituent elements such as In, [45,49] doped with metals such as Ti, [54] or composed of a conductive material such as ITO [55] ) intended to enhance the TFT electrical performance.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing interest in solution-processed oxide semiconductors, TFTs with high electrical mobilities of over 30 cm·V −1 s −1 and low driving voltages of less than 2 V have been reported [ 10 , 11 ]. Moreover, studies on process developments such as atomic composition ratio, doping, and chemical treatment have remarkably improved TFT performance [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the morphological and film thickness characteristics play a more decisive role, depending on the crystal structure. Although studies on the solution-processed IZO TFT have focused on the electrical improvement [ 10 , 11 , 12 , 13 ] in solution-processed oxide semiconductors, because the atomic bonding structure is rearranged via processes such as solvent evaporation, thermal decomposition, and condensation reactions, the crystallinity is further influenced by the reaction pathways [ 30 ]. Therefore, to discuss a one-step forward analysis such as bias-stress mechanisms of TFT, it is essential to understand the trap state distribution and charge transport mechanism based on the atomic bonding structure; however, such an understanding has not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…15 It has been reported that the electronegativity difference between nitrogen (N, 3.04) and oxygen (O, 3.44) results in a higher binding energy of the In 3d, Ga 2p, and Zn 2p spectra when binding nitrogen with the corresponding metal. 63 A more detailed discussion on this will be presented later in this paper.…”
mentioning
confidence: 99%